Validitas E-Modul Berbasis Problem Based Learning pada Materi Perubahan Lingkungan Kelas X SMA/MA - Meldrawati Meldrawati; Erismar Amri; Evrialiani Rosba (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Developments in technology and information affect the management of teaching materials. E-Module is one of the innovative digital teaching materials that can be used to support the learning process. The purpose of this research is to produce a valid E-Module. This research was conducted at the Department of Biology Education, Faculty of Science and Technology, West Sumatra PGRI University using a 4D model (Define, Design, Development, and Disseminate). However, this research only reached the development stage. The assessment instrument used is the E-Module validation sheet. The data obtained were analyzed by descriptive quantitative. Based on the results obtained from material experts, media experts, and Biology teachers, it shows an average score of 98.5% which is seen from the feasibility of content, language, didactics, and graphics. Based on these results it can be concluded that the problem-based learning-based E-Module produced is very valid and suitable for use as teaching material.